Differences of Performance Measurement in Mutual Funds and Their Impact on Investment Decisions - Sandhika Cipta Bidhari; Rika Oktavia (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study discusses the performance of mutual funds in the capital market, divided into conventional and sharia mutual funds. The population of this research is all mutual funds, both conventional and sharia, which are traded on the Bibit application platform. Total of 77 conventional mutual funds and 31 sharia mutual funds. Based on sampling, 17 conventional mutual funds and 9 sharia mutual funds were obtained. The research observation period spans from 2021 to 2023. This research uses a quantitative approach with the Risk-Adjusted Return method, consisting of the Sharpe, Treynor, and Jensen methods. Then it will analyze the differences in performance between conventional and sharia mutual funds. The Mann-Whitney U Test is the analysis technique employed using SPSS 25. The results showed that there was no difference in performance between conventional mutual funds and sharia mutual funds based on the Shape, Treynor, and Jensen methods.